The Effectiveness of Ozone Therapy in Pharyngocutaneous Fistula of Irradiated Necks: An Experimental Animal Study - Muz, Sami Engin; Ercelik, Onur; Olgun, Pelin Samaraz; Muz, Arzu; Kurtman, Cengiz; Kilinc, Ilyas Anil; Eroksuz, Yesari (Wolters Kluwer Medknow Publications, 2025)
Purpose:This investigation aimed to examine the effects of systemic ozone therapy on healing in a rat model of irradiated pharyngocutaneous fistula (PCF).Materials and Methods:A total of 24 rats were randomly assigned to two groups. The control group (n = 12) did not receive any additional intervention following the administration of a total dose of 18 Gray of radiotherapy (RTx), and the fistula was opened 7 days later. In the study group (n = 12), the fistula was opened 7 days after a total RTx dose of 18 Gy, followed by rectal ozone therapy for 7 days. Subsequently, the histopathological alterations in the fistula tissue were evaluated.Results:The control and ozone groups exhibited successful fistula formation following RTx. During the observation period, six out of seven rats in the control group exhibited persistent fistula formation, whereas only one rat in the ozone group demonstrated fistula formation. The histological findings demonstrated that the ozone group exhibited statistically significant fibroblastic activity, inflammatory infiltration, and vascularization (P = 0.005, P = 0.037, P = 0.003, respectively).Conclusion:Ozone treatment should be considered as a potential therapeutic option for the treatment of complications associated with PCF following radiation therapy, given its efficacy and viability.
Keywords: Fistula; laryngectomy; ozone; radiotherapy